1997
DOI: 10.1258/0956462971920820
|View full text |Cite
|
Sign up to set email alerts
|

Intracavitary contact X-ray therapy of oral HIV-associated Kaposi's sarcoma

Abstract: A retrospective study was performed to assess the efficacy and low mucosal toxicity of intracavitary contact X-ray therapy (ICRT), a proposed treatment of small/medium sized lesions of oral HIV-associated Kaposi's sarcoma (HIV-KS). Twenty-six patients with histologically confirmed oral HIV-KS underwent ICRT in the period 1986-1995. No patient received antiblastic or interferon therapy during the radiotherapy or follow-up periods. ICRT was performed according to the usual technical modalities of contact X-ray t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The study done on a relevant number of irradiated lesions and with a long follow-up has made us to confirm and define better some observations reported in previous articles of ours on the topic. [7][8][9] Even if with different intentions, curative as far as possible in spite of the multicentric features for Mediterranean KS, and palliative or reducing the extent of the disease in HIV-related KS, radiotherapy has confirmed to be a safe and effective method, as established by some of the most reliable reports of the literature. [10][11][12][13] On the other hand, it has been frequently observed that patients treated with extended field irradiation suffer from severe skin reactions (exudative epidermitis with skin ulcerations) in 5% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…The study done on a relevant number of irradiated lesions and with a long follow-up has made us to confirm and define better some observations reported in previous articles of ours on the topic. [7][8][9] Even if with different intentions, curative as far as possible in spite of the multicentric features for Mediterranean KS, and palliative or reducing the extent of the disease in HIV-related KS, radiotherapy has confirmed to be a safe and effective method, as established by some of the most reliable reports of the literature. [10][11][12][13] On the other hand, it has been frequently observed that patients treated with extended field irradiation suffer from severe skin reactions (exudative epidermitis with skin ulcerations) in 5% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, radiation‐induced oral toxicities, such as severe mucositis, impaired salivary gland function, taste disturbances, and the exacerbation of oral infections frequently develop early in the course of therapy and with relatively low doses of radiation, necessitating palliative measures . Modified radiotherapy techniques such as intracavitary contact radiation, by contrast, have been efficacious in the treatment of OKS and are associated with negligible mucositis . In current practice, external beam radiotherapy is generally reserved for the treatment of symptomatic or obstructive oropharyngeal KS …”
Section: Treatmentmentioning
confidence: 99%
“…44 Modified radiotherapy techniques such as intracavitary contact radiation, by contrast, have been efficacious in the treatment of OKS and are associated with negligible mucositis. 45 In current practice, external beam radiotherapy is generally reserved for the treatment of symptomatic or obstructive oropharyngeal KS. 20,44 Although local and regional OKS may respond to conservative measures, symptomatic OKS, epidemic OKS that is unresponsive to HAART, and disease that has disseminated to visceral organs often require systemic intervention.…”
Section: Treatmentmentioning
confidence: 99%
“…Margaretic et al [17] describe the successful use of total skin electron treatment for extensive cutaneous lesions. For mucosal foci, Caccialanza et al [18] reported an intracavitary X-ray therapy using soft X-rays whereas Syndikus et al [19] applied brachytherapy to the hard and soft gum using individual dental plates.…”
Section: Technique Of Radiotherapymentioning
confidence: 99%